Free wheat flour lipids decrease air-liquid interface stability in sponge cake batter. (February 2021) - Pycarelle, Sarah C.; Bosmans, Geertrui M.; Pareyt, Bram; Brijs, Kristof; Delcour, Jan A.
Graphical abstract: Highlights: Prior removal of flour lipids (FLs) improves foaming of sponge cake batter. Air-liquid interfaces in sponge cake batter from defatted flour contain less lipid. Free FLs decrease the stability of the protein-dominated interface in batter. Relocation of FLs makes them more available for adsorption at air-liquid interfaces. Relocation of FLs lowers initial protein adsorption at air-liquid interfaces. Abstract: The impact of free wheat flour lipids on air-liquid interface stability during sponge cake making was investigated. Therefore, the molecular population at the air-liquid interface in batters prepared with flour of which part of the lipids had been either relocated or removed prior to batter preparation was determined. Surface-active molecules were isolated from batter using a foam separation protocol. Diluted batter was whipped and the resulting foam was used as model system for the air-liquid interface in sponge cake batter. Relocating flour lipids prior to batter making enabled them to adsorb at the air-liquid interface in the foam. This limited the degree of protein adsorption at the air-liquid interface, but it did not impact the composition of the adsorbed protein population. Removing flour lipids prior to batter making resulted in foam containing relatively higher levels of lipids mainly originating from egg yolk. Prior removal of flour lipids impacted neither foam protein content nor foam protein composition. The resultant molecular population improved air-liquid interface stability in sponge cake batter. Thus, free wheat flour lipids and wheat flour lipids set free by solvent treatment decrease air-liquid interface stability in sponge cake batter mainly because they limit protein adsorption and, as such, interfere with the protein-dominated interface.